2018
DOI: 10.1213/ane.0000000000002732
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Variation in Anesthetic Drug Costs

Abstract: The majority of the variation was not described by the models, possibly indicating high per-case random variation. The largest sources of variation identified by our models included attending anesthesiologist, procedure type, and case duration. The difference in cost between institutions was statistically significant but was minor. While many prior studies have found significant savings resulting from cost-reducing interventions, our findings suggest that because the overall cost of anesthetic drugs was small,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…For long-duration general anesthesia using remimazolam, the anesthetic drug cost in Japan may be about 1.5 times or more compared to that of propofol. Wanderer et al [ 18 ] investigated the significant contributors to variation in anesthetic drug cost and concluded that the overall cost of anesthetic drugs was low and that cost-saving efforts may be better focused elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…For long-duration general anesthesia using remimazolam, the anesthetic drug cost in Japan may be about 1.5 times or more compared to that of propofol. Wanderer et al [ 18 ] investigated the significant contributors to variation in anesthetic drug cost and concluded that the overall cost of anesthetic drugs was low and that cost-saving efforts may be better focused elsewhere.…”
Section: Discussionmentioning
confidence: 99%